PROGRAM RELAWAN PAJAK MEMODERASI HUBUNGAN MOTIVASI KARIER DAN MOTIVASI EKONOMI TERHADAP MINAT BERKARIER DI BIDANG PERPAJAKAN (STUDI PADA RELAWAN PAJAK DI BALI): Perpajakan - MADE DWI ARIASA; I Nyoman Putra Yasa; I Gede Putu Banu Astawa (Universitas Pendidikan Ganesha, 2025)
This research aimed to examine the influence of career motivation and economic motivation on students’ interest in pursuing a career in taxation, with the Tax Volunteer Program serving as a moderating variable among students participating in the program. The study employed a proportionate stratified random sampling technique, involving 66 students from a total population of 204 across seven universities in Bali in 2025, selected using the Slovin formula. Primary data were collected through questionnaires. The findings show that both career motivation and economic motivation have a positive effect on students’ career interest in taxation. Furthermore, the Tax Volunteer Program plays a moderating role in strengthening the relationship between these motivations and career interest in the field of taxation.